2008
DOI: 10.1017/s0003598x00096460
|View full text |Cite
|
Sign up to set email alerts
|

Medieval élite burials in eastern Mecklenburg and Pomerania

Abstract: High status burial remains one of archaeology's most evocative types of site – but it is not always easy to know why they were built, where and when they were. The author describes a group of élite burials that appeared in north Europe in the late eleventh-twelfth century in a historical context that is unusually clear, and proposes the rise of a pagan élite in the face of aggressive Christianisation from the neighbours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
1
1
0
2
Order By: Relevance
“…Recent analysis of the distribution of Western Slavic chamber graves in the Piast state has shown that they are predominantly located close to major strongholds and supra-local centres of political, administrative, and religious power (Błaszczyk, 2016: 38). Their chronology is also significant for the present discussion, as they emerge in the tenth–eleventh centuries and continue to be built in the coastal areas of Pomerania until the eleventh–twelfth centuries (Biermann, 2008), which fits what we know from textual sources about the social and political transformations and the process of state formation in these areas. In view of their chronology, distribution, and wealth (see below), there are strong reasons to identify chamber graves with the final resting places of elites.…”
Section: ‘Materials Markers’ Of Western Slavic Elite Identity In Stronsupporting
confidence: 61%
See 1 more Smart Citation
“…Recent analysis of the distribution of Western Slavic chamber graves in the Piast state has shown that they are predominantly located close to major strongholds and supra-local centres of political, administrative, and religious power (Błaszczyk, 2016: 38). Their chronology is also significant for the present discussion, as they emerge in the tenth–eleventh centuries and continue to be built in the coastal areas of Pomerania until the eleventh–twelfth centuries (Biermann, 2008), which fits what we know from textual sources about the social and political transformations and the process of state formation in these areas. In view of their chronology, distribution, and wealth (see below), there are strong reasons to identify chamber graves with the final resting places of elites.…”
Section: ‘Materials Markers’ Of Western Slavic Elite Identity In Stronsupporting
confidence: 61%
“…Various motivations may have incited people to construct chamber graves. While some scholars see this form of funerary architecture as characteristic of ‘barbaric’ societies at the time of state formation and conversion (Rębkowski, 2007: 159; Błaszczyk, 2016: 42), others argue that it reflects the ideological struggle associated with the decline of pagan ideologies (Biermann, 2008). Still others point out that the emergence of chamber graves may be the result of several processes that are difficult to resolve (Janowski, 2015: 91–92).…”
Section: ‘Materials Markers’ Of Western Slavic Elite Identity In Stronmentioning
confidence: 99%
“…Poczynione ustalenia zostały dostrzeżone w literaturze przedmiotu, nie tylko polskiej, wywołując zróżnicowaną w konkluzjach dyskusję (Leciejewicz 1993;Leciejewicz 1994Leciejewicz /1995Skalski 1995;Kajzer 1996, s. 105 i n.;Zoll-Adamikowa 1997a;1997b;łosiński 1999;Duczko 2000;Wołoszyn 2004;Buko 2005, s. 350 i n.;Kordala 2006;Biermann 2008;Rohrer 2012;Goßler 2013;Goßler 2014). W charakterze inspiracji lub badawczych odniesień odnajdujemy je w pracach opublikowanych po roku 2000, w których omówione zostały wyniki analiz archeologicznych wyżej wymienionych grobów birytualnego cmentarzyska w Lutomiersku pod łodzią czy położonych nad środkowo-dolną Wisłą szkieletowych cmentarzysk z Bodzi pod Włocławkiem, z Kałdusa na ziemi chełmińskiej oraz z Ciepłego na Pomorzu Wschodnim (Chudziak 2001;Ratajczyk 2013;Grygiel 2014;Buko [red.]…”
Section: Rys Joanna Sawickaunclassified
“…Innego rodzaju sceptycyzm poznawczy, tym razem dotyczący możliwości formułowania przez archeologię wiarygodnych ustaleń w zakresie etnokulturowych atrybucji odkrywanych przez nią grobów, towarzyszy z kolei badaczom, którzy uwagę skoncentrowali na rozpoznaniu genezy fenomenu wczesnośredniowiecznych grobów komorowych na obszarze wschodniej i środkowej części Europy (Sikora 2009, s. 154 i n.;2013a;2013b;Janowski 2015;Błaszczyk 2016;zob. też Brather 2004;Biermann 2008;Rohrer 2012). Reprezentują oni poglądy w pewnym zakresie zróżnicowane, wyraźnie jednak inspirowane tezami prac dwu znanych archeologów niemieckich średniego pokolenia: Sebastiana Brathera oraz Felixa Biermanna.…”
Section: Rys Joanna Sawickaunclassified